Study of microalbuminuria in essential hypertension patients with target organ damage - Bakhtar, Vijay; Bakhtar, Niyati; Pandey, Kirit; Pandey, Neha (International Journal of Research in Medical Sciences, 2020)
Background: Urinary albumin excretion has been purported to be strongly linked to cardiovascular events in hypertensive patients. The prevalence of microalbuminuria in patients with essential hypertension and its relationship with target organ damage was evaluated with the present study, as the correlation of microalbuminuria and target organ damage except cardiovascular events has not been deliberated upon much in the past. Methods: One hundred and twenty cases of essential hypertension were enrolled sequentially. Prevalence of urinary albumin excretion and its correlation with target organ damage (left ventricular hypertrophy, retinopathy and stroke) was analyzed. Urinary albumin excretion was assessed by turbidimetry method, while microalbuminuria was calculated by urine albumin to creatinine ratio. Results: Microalbuminuria was observed in 57.7% cases of essential hypertension. Target organ damage was observed in 62.5% (75) patients, out of which 78.66% patients had associated microalbuminuria (p<0.05). Higher prevalence was observed in patients with longer duration and greater severity of hypertension, increased body mass index and dyslipidemia. Conclusions: The assessment of microalbuminuria in hypertensive patients is a great value addition for the evaluation of target organ damage. Prompt control of hypertension and lipid levels along with weight management may lead to decreased risk of microalbuminuria.